Review of video transcoding for network video applications - YU Sheng-fa; CHEN Zeng-ping; ZHUANG Zhao-wen (Tongxin xuebao, 2007)
The technical issues about video transcoding,especially the three typical architectures were firstly outlined and compared.Emphasis was put on how to reduce the complexity and improve the video quality by exploiting the informa-tion,which can be easily extracted from the input video bitstream.Other active research topics in recent years such as in-formation,especially watermark and error resilient data,insertion transcoding and H.264 bitstream related video transcoding were discussed in detail.Future directions on this topic were also prospected.